Systematic review on the relationship between the use of oral contraceptives and Vulvovaginal Atrophy (VVA): Effects, symptoms and implications on the quality of life of patients - Moliterno, Amanda; Piccoli, Maria Victoria Ferreira (Seven Editora, 2023)
Vulvovaginal atrophy (AVV) is a frequent condition in the postmenopausal period and has been associated with the use of oral contraceptives due to the disruptions in hormone levels that these medications can cause. However, the amount of data available on this relationship is limited due to underreporting of cases. DOI:https://doi.org/10.56238/uniknowindevolp-015